Development and validation of an inventory for Western Cape primary science teachers' conceptions of formative assessment - Ghorpade, Aparna Sandeep (School of Education, 2025)
Across many nations worldwide, formative assessment has become an increasingly important component of education policies. Adopting a formative assessment approach in education can improve learners' academic performance, ultimately leading to enhanced educational outcomes. The current South African assessment policy (DBE, 2011) emphasises using formative assessment in primary schools, highlighting its importance in the educational process. However, studies exploring South African teachers' formative assessment practices have shown the need to improve teachers' understanding and use of formative assessments in classrooms. Therefore, it is important to make South African teachers' conceptions of assessment explicit in order to determine their current understanding of formative assessment and to move them towards implementing appropriate approaches to formative assessment. In South Africa, limited research has been conducted exploring teachers' conceptions of assessment, especially in Natural Sciences and Technology at the Intermediate Phase (Grades 4-6) level. Consequently, this study has four objectives - a) to develop an instrument suitable for use with primary school science teachers in the Western Cape, b) to identify practicing primary school science teachers' conceptions of formative assessment, c) to identify the demographic factor(s) that influence the conception of formative assessment of primary school science teachers, and d) to identify the preferred formative assessment practices of such primary school science teachers. Data were collected using a quantitative research design. The survey instrument used was developed by adapting Brown's (2006) Abridged Teachers' Conceptions of Assessment (TCoA-IIIA) inventory for the Western Cape context. Relevant science education stakeholders from the Western Cape province evaluated the content validity of the TCoA-IIIA questionnaire by providing feedback on the clarity of instructions and items of the questionnaire. The modifications and adaptation of TCoA-IIIA resulted in the “Teachers' Conceptions of Assessment - Western Cape (TCoA-WC)” questionnaire. To adapt the TCoA-IIIA for use in the Western Cape, rigorous cross-cultural adaptation and back-translation methods were followed. English, Afrikaans, and isiXhosa are the most commonly spoken languages in the Western Cape province. Hence, a pilot test of the TCoA-WC was conducted with a group of English, Afrikaans, and isiXhosa teachers. The TCoA-WC was then administered online to teachers in 65 schools across four Metro Education districts in the Western Cape. A stratified random sampling method was used as a method of sampling. The selected districts for the study included Metro Central, Metro North, Metro East, and Metro South, which collectively 64% of the province's teacher population. The data collection stage of the present study coincided with the first year of the COVID-19 pandemic, resulting in a limited response of 157 primary science teachers. These 157 responses were analysed by conducting three types of statistical analyses. The confirmatory factor analysis (CFA) analysis of data collected using TCoA-WC revealed the same factor structure as that of the TCoA-IIIA model, confirming the presence of four main conceptions of assessment (i.e., Improvement, School Accountability, Learner Accountability, and Irrelevance) and associated 27 items in the thinking of Western Cape primary science teachers. The TCoA-WC model also exhibited well-fitted psychometric properties. The reliability analysis and CFA analysis confirmed that TCoA-WC is a valid and reliable measure of Western Cape primary science teachers' conceptions of formative assessment. Thus, this study resulted in the development of the TCoA-WC inventory, which is conceptually, linguistically, and culturally appropriate for use with the teachers in the Western Cape province. The study participants did not explicitly endorse any specific assessment concept identified by the TCoA-WC inventory. However, the CFA analysis confirmed that all four conceptions of assessment, that is, Improvement, School Accountability, Learner Accountability, and Irrelevance, are present in the thinking of Western Cape primary school science teachers. It is hoped that the skillful integration of the findings of this study into teacher professional development initiatives will result in the implementation of formative assessment practices in the Western Cape primary classroom as outlined in the Curriculum and Assessment Policy Statement (DBE, 2011), which will lead to significant improvement in the performance of learners